2007
DOI: 10.1007/s10096-007-0384-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hepatitis C virus coinfection on immune restoration during successful antiretroviral therapy in chronic human immunodeficiency virus type 1 disease

Abstract: The effect of coinfection with hepatitis C virus (HCV) on immune restoration in 39 human immunodeficiency virus (HIV)-infected patients during treatment with combined antiretroviral therapy (cART) was prospectively evaluated. After 48 weeks of treatment, HCV-coinfected patients had lower increases in CD4% (P = .05), total CD4+ (P = .01), and naïve CD4+ (P = .06) T cells than did single-infected subjects. Higher baseline naïve CD4+ T-cell levels were associated with better CD4+ (P = .05) and naïve CD4+ (P < .00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 29 publications
1
24
0
4
Order By: Relevance
“…Specifically, studies have shown that the presence of HCV can blunt the CD4 recovery. Though there is not agreement on all studies whether HCV coinfection leads to decreased number of CD4 cell recovery [1523], there does appear to be a delayed CD4 reconstitution associated with HIV/HCV coinfected patients undergoing HAART therapy [2427]. In addition, HCV infection has been cited as a risk factor for developing an AIDS-defining illness [28].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, studies have shown that the presence of HCV can blunt the CD4 recovery. Though there is not agreement on all studies whether HCV coinfection leads to decreased number of CD4 cell recovery [1523], there does appear to be a delayed CD4 reconstitution associated with HIV/HCV coinfected patients undergoing HAART therapy [2427]. In addition, HCV infection has been cited as a risk factor for developing an AIDS-defining illness [28].…”
Section: Discussionmentioning
confidence: 99%
“…HBV and HCV are of concerns because both viruses compromise liver function, which may further affect the metabolism and therapeutic effect of antiretroviral drugs (ARV) for AIDS patients (11)(12)(13). They are also classified as group one causative agents of hepatocellular carcinoma (HCC) by International Agency for Research on Cancer (IARC).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the role of HCV coinfection in the clinical and viroimmunological outcomes of HIV‐1 infection is controversial and has not yet been elucidated despite the many studies published. Some studies have reported poorer immunological [3–15] and clinical outcomes [2,4–6,16–21] in patients coinfected with HIV‐1/HCV as compared with HIV‐1‐monoinfected patients, whereas others found that there were no differences in immunological [3,19–35], virological [4–8,31–34] and clinical endpoints [1,7,28–33,36,37] between these two groups.…”
Section: Introductionmentioning
confidence: 99%